Initial reactivity differences between a 3-component surrogate model and a 24-component model for RP-1 fuel pyrolysis evaluated by ReaxFF MD. (15th June 2018) - Han, Song; Li, Xiaoxia; Zheng, Mo; Guo, Li
Highlights: Pyrolysis reactivity differences of two RP-1 models were evaluated by ReaxFF MD. A 3-component surrogate model and a complex 24-component model were employed. Versatile ring opening pathways in the 24-component model have been revealed. Reaction pathway differences for formation of 2-methylpropene, dienes, cyclohexenes. An alternative approach for evaluating comprehensive reactivity in fuel pyrolysis. Abstract: This work attempts to investigate initial reactivity for pyrolysis of a rocket propellant fuel (RP-1) by reactive molecular dynamics simulations with ReaxFF force field. The initial reactivity differences between a 3-component surrogate model and a more complex 24-component model have been observed in a series of heat-up and isothermal pyrolysis simulations performed using the GPU-enabled code GMD-Reax. The RP-1 conversion in the 3-component surrogate is slower than that of the 24-component model. The maximal weight fraction difference for RP-1 consumption can be up to 21.2% in heat-up simulations and 22.3% in isothermal simulations. The reaction analysis facilitated by the code VARxMD further reveals the differences of pyrolysis intermediates, products, and reaction pathways between the two RP-1 models. Normal paraffin reactions are similar between the two RP-1 models owing to the similar fuel structures of normal alkanes. For branched paraffin reactions, the pyrolysis of the multi-branched fuel component of iso -cetane in the 3-component surrogate will produce 2-methylpropene, which is not a major pyrolysis product in the 24-component model mainly due to lack of quaternary carbon with methyl side chains in the branched paraffin components. Compared to the reactions of methylcyclohexane, the only cycloparaffin in the 3-component surrogate, more versatile ring opening reactions of cycloparaffins can occur in the 24-component model that will generate more dienes and cyclohexene from the double-ring fuel structures. This work suggests that the reactive molecular dynamics simulations of multi-component model with rich chemical structures closer to real fuel components have the potential as an alternative approach for evaluating reactivity in fuel pyrolysis.